Optimasi Distribusi Makan Bergizi Gratis berbasis Vehicle Routing Problem with Time Windows (VRPTW) - Irwan Syahputra; Anzas Ibezato Zalukhu; Suhardiansyah; Maida Indrayani; Ayu Ofta Sari; Dewi Sartika; Bambang Sugito (Management of Information System Journal, 2026)
The Free Nutritious Meal Program (MBG) requires an efficient distribution system to ensure the timely delivery of meals while maintaining food quality and safety. This study aims to implement the Vehicle Routing Problem with Time Windows (VRPTW) method in a web-based MBG Distribution Information System to optimize delivery routes based on vehicle capacity, demand quantity, destination locations, and service time window constraints. The research methodology consisted of problem identification, literature review, data collection, system design, implementation, and system evaluation. The study utilized operational data from the Nutrition Fulfillment Service Unit (SPPG) in Desa Baru Pasar VIII, Tanjung Beringin, Langkat Regency, serving 13 schools with a total demand of 1,672 meal portions using two delivery vehicles. The implementation results showed that the VRPTW method generated an optimized distribution route with a total travel distance of 42.74 km. The evaluation results demonstrated that VRPTW reduced the total travel distance from 49.86 km to 42.74 km, representing a 14.28% improvement in distribution efficiency. Furthermore, the total distribution time decreased from 118 minutes to 101 minutes, achieving a 14.41% reduction compared with the conventional distribution method. In addition, the system automated route planning, minimized route overlap, and improved vehicle capacity utilization. These findings indicate that integrating the VRPTW method into the MBG Distribution Information System enhances operational efficiency and supports more effective and timely meal distribution.